2012
DOI: 10.1016/j.gie.2012.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biliary stents on EUS-guided FNA of pancreatic mass lesions

Abstract: Background Few studies have evaluated the impact of biliary stents on EUS-guided FNA. Aim To compare diagnostic yield of EUS-FNA in patients with or without biliary stents. Design Retrospective study. Setting Tertiary referral center. Patients Patients with obstructive jaundice secondary to solid pancreatic mass lesions who underwent EUS-FNA over 5 years. Main Outcome Measures The primary objective was to compare the diagnostic accuracy of EUS-FNA in patients with or without biliary stents and betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 13 publications
4
43
1
Order By: Relevance
“…This was not proved in our group, perhaps due to the fact that there were only three patients with chronic pancreatitis features. The presence of biliary plastic stents has been reported to diminish the rate of EUS-FNA [30], but it did not influence our results, although biliary stents were seen in about 10% of our cases, as in the other study [30]. As already known from the cytology assessment, the diagnostic accuracy of core biopsy is not related to the mass size or the presence of necrosis inside, facts previously reported also by our group [21,[31][32][33].…”
Section: Discussionsupporting
confidence: 69%
“…This was not proved in our group, perhaps due to the fact that there were only three patients with chronic pancreatitis features. The presence of biliary plastic stents has been reported to diminish the rate of EUS-FNA [30], but it did not influence our results, although biliary stents were seen in about 10% of our cases, as in the other study [30]. As already known from the cytology assessment, the diagnostic accuracy of core biopsy is not related to the mass size or the presence of necrosis inside, facts previously reported also by our group [21,[31][32][33].…”
Section: Discussionsupporting
confidence: 69%
“…If transpapillary tissue sampling is non‐diagnostic or if early biliary drainage is unnecessary, we recommend EUS‐FNA to secure the pathological diagnosis, especially when the DBS is associated with a mass. Despite concerns that the presence of a biliary stent may compromise the accuracy of EUS imaging, most studies have reported that an indwelling biliary stent does not adversely affect the diagnostic yield of EUS‐FNA . Alternatively, EUS and ERCP may be performed in a single session for evaluation of obstructive jaundice as a result of a pancreatic mass .…”
Section: Methodsmentioning
confidence: 99%
“…Cytologic diagnosis with EUS‐FNA has been studied extensively, with widely varying sensitivity . The sensitivity has been reported to range from 14% to 100%, whereas specificity has ranged from 69% to 100% .…”
Section: Introductionmentioning
confidence: 99%